ENZYMATIC HYDROLYSIS AND GLYCEMIC ASSESSMENT OF THE CARBOHYDRATES IN SOME NATURAL TURKISH INDIGENOUS FOODSTUFFS IN SIMULATED SYSTEM - Yusufoglu, Busra; Yaman, Mustafa; Karakus, Emine (YILDIZ TECHNICAL UNIV, 2020)
It is important to understand the benefits of an indigenous foodstuff containing carbohydrate in terms of glycemic. The glycemic parameters are the glycemic index (GI) and glycemic load (GL). Turkish Kahramanmaras tarhana and Beypazan cookie were used as indigenous foodstuffs. Because of delicious and high protein content, these foods are commonly used in Turkey. In this study, we realized the glycemic assessment of these foodstuffs by carrying out enzymatic hydrolysis of the carbohydrates containing in our simulated in vitro system. It was found that Kahramanmaras Tarhana as used snack and soup have a lowglycemic index (<55) using Turkish white bread (TWB) as a reference carbohydrate. The GI values of Beypazan Cookie and Turkish Kahramanmaras Tarhana were determined as 62.8 +/- 2.8 and 53.1 +/- 2.4, respectively. The glycemic load (GL) values of both samples were bigger than 20. The values of these species will increase if their consumption is high.
Keywords: Glycemic assessment; indigenous foodstuff; simulated digestion; Kahramanmaras tarhana; Beypazari cookie; IN-VITRO; INDEX; DIGESTION; Engineering